Anti-dazzle film and preparation method and application thereof

By using hydrophobic polycaprolactone copolymer, tanninic microspheres, crosslinking agents and plasticizers in car coat films, the problem of insufficient performance of traditional car coat films in anti-glare and heat insulation is solved, and an efficient combination of anti-glare and heat insulation effect is achieved, improving driving safety and comfort.

CN119842238APending Publication Date: 2025-04-18GUANGZHOU KAWEI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510049339.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Traditional car coat films have insufficient performance in anti-glare and heat insulation, and cannot effectively reduce glare and high temperatures in the car, affecting driving safety and comfort.

Method used

The hydrophobic polycaprolactone copolymer is used to enhance the hydrophobic properties, weather resistance and mechanical properties of the film by introducing perfluoropolyether segments; the use of tanninic microspheres as scatterers to reduce reflectivity and improve thermal insulation; the crosslinking agent enhances the physical stability of the film; and the plasticizer adjusts the flexibility and processing properties of the film.

Benefits of technology

It significantly reduces glare, improves driving safety, improves thermal insulation performance, improves riding comfort, and optimizes self-cleaning functions to reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of films, in particular to an anti-dazzle film and a preparation method and application thereof. The invention discloses an anti-dazzle film, which is prepared from the following raw materials in parts by weight: 50 to 60 parts of hydrophobic polycaprolactone copolymers, 5 to 8 parts of tannic acid microspheres, 10 to 15 parts of cross-linking agents, 15 to 20 parts of plasticizers and 120 to 150 parts of mixed solvents. According to the anti-dazzle film disclosed by the invention, the hydrophobic polycaprolactone copolymer is introduced into a perfluoropolyether chain segment, so that the hydrophobic property, the weather resistance and the mechanical property of the film are improved; the tannic acid microspheres are used as scatterers, so that the reflectivity is reduced by scattering light, the glare phenomenon is reduced, and meanwhile, the heat insulation property is improved; the cross-linking agent enhances the cross-linking density in the film and improves the physical stability; the plasticizer adjusts the flexibility and processability of the film, and the film solves the problem that a traditional car cover film is insufficient in anti-dazzle and heat insulation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of films, and in particular to an anti-glare film and a preparation method and application thereof. Background Art

[0002] At night or in strong light conditions, glare can seriously affect the driver's vision and increase the risk of traffic accidents, so anti-glare performance is very important for driving safety. Although traditional car cover films can reduce glare to a certain extent, the effect is not ideal, especially under strong sunlight or artificial light, it will still produce dazzling reflected light. Therefore, improving the anti-glare performance of the film and reducing the interference of glare on the driver's vision is one of the technical problems that need to be solved urgently.

[0003] In addition, thermal insulation performance is also an important technical indicator of car cover films. In a high temperature environment, the temperature of the car body will rise rapidly, which not only affects driving comfort, but may also cause damage to the electronic equipment and interior materials inside the vehicle. Traditional car cover films have limited thermal insulation performance and cannot effectively block the transfer of external heat, resulting in excessively high temperatures inside the car, requiring more energy to maintain a suitable driving environment. Therefore, the development of film materials with high thermal insulation performance to reduce the temperature of the car body and improve driving comfort and energy saving is a hot topic in current industry research.

[0004] The main technical route to solve the problems of anti-glare and heat insulation technology is to modify the film material or add specific functional additives. However, the added functional additives may affect other properties of the film, such as reduced transparency, resulting in a decrease in the overall performance of the film. In addition, the existing modified films still need to be improved in terms of anti-glare and heat insulation effects, and cannot meet the growing market demand.

[0005] Therefore, in view of the problem that the films currently used in car covers have relatively poor anti-glare and heat-insulating performance, it is necessary to develop an anti-glare film and a preparation method thereof to improve the anti-glare and heat-insulating properties of the film to meet the development needs of the automotive industry. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present application describes an anti-glare film and its preparation method and application. The hydrophobic polycaprolactone copolymer improves the hydrophobicity, weather resistance and mechanical properties of the film by introducing perfluoropolyether segments; tannic acid microspheres act as scatterers to reduce reflectivity and glare by scattering light, while improving thermal insulation; the cross-linking agent enhances the cross-linking density inside the film and improves physical stability; the plasticizer adjusts the flexibility and processing properties of the film; the anti-glare film described in the present application solves the problem of insufficient anti-glare and thermal insulation performance of traditional car cover films.

[0007] The technical solution provided by this application is:

[0008] In a first aspect, the present application provides an anti-glare film, comprising the following raw materials in parts by weight:

[0009] 50-60 parts of hydrophobic polycaprolactone copolymer, 5-8 parts of tannic acid microspheres, 10-15 parts of cross-linking agent, 15-20 parts of plasticizer, and 120-150 parts of mixed solvent.

[0010] In one or more technical solutions, the method for preparing the hydrophobic polycaprolactone copolymer comprises the following steps:

[0011] The perfluoropolyether carboxylic acid was dissolved, dicyclohexylcarbodiimide was added, the temperature was raised to 40°C under nitrogen protection, and the reaction was carried out at 40°C for 2 hours; polycaprolactone was continuously added, and the reaction was continued at 40°C for 5 hours. After the reaction was completed, post-treatment was carried out to obtain a hydrophobic polycaprolactone copolymer.

[0012] In one or more technical solutions, the molar ratio of the perfluoropolyether carboxylic acid, dicyclohexylcarbodiimide and polycaprolactone is 1:1:0.1.

[0013] Furthermore, in the above technical solution, a hydrophobic polycaprolactone copolymer with excellent hydrophobic properties is prepared by introducing perfluoropolyether carboxylic acid into the polycaprolactone molecular chain. The hydrophobic polycaprolactone copolymer can not only improve the waterproof performance of the film surface, but also enhance the weather resistance and mechanical properties of the film. At the same time, the hydrophobic polycaprolactone copolymer helps to reduce the adhesion of pollutants such as raindrops and dust to the film surface, thereby improving the self-cleaning ability.

[0014] Specifically, the hydrophobic polycaprolactone copolymer is 50-60 parts, which can ensure that the film has good physical and chemical stability. If the amount of the hydrophobic polycaprolactone copolymer exceeds 60 parts, it may affect the effect of other additives, such as the dispersibility of tannic acid microspheres; if the amount of the hydrophobic polycaprolactone copolymer is less than 50 parts, it may lead to insufficient mechanical strength of the film.

[0015] In one or more technical solutions, the particle size of the tannic acid microspheres is 10-50 μm.

[0016] In one or more technical solutions, the method for preparing tannic acid microspheres comprises the following steps:

[0017] Tannic acid and ethylene glycol diglycidyl ether were dissolved, triphenylphosphine was added, the mixture was fully mixed, and the mixture was reacted at room temperature for 24 hours. After the reaction, the reaction liquid was centrifuged at a speed of 3000 rpm, the microspheres were collected, and then post-processed to obtain tannic acid microspheres.

[0018] Furthermore, in the above technical solution, tannic acid is a natural polyphenol compound, which can increase the mechanical strength of the film and improve its optical properties by reacting with ethylene glycol diglycidyl ether to form a cross-linked network structure. Tannic acid microspheres in the film scatter light, thereby reducing reflectivity and glare, and can also improve thermal insulation.

[0019] In the above technical solution, the particle size of tannic acid microspheres is 10-50μm, and 10-50μm tannic acid microspheres can effectively scatter light in the film, thereby reducing glare. If the amount of tannic acid microspheres exceeds 8 parts, the transparency of the film may decrease, affecting visual clarity; if the amount of tannic acid microspheres is less than 5 parts, it may not be able to effectively reduce the glare effect.

[0020] In one or more technical solutions, the mixed solvent is a mixed solvent composed of DMF and THF in a mass ratio of 1: 1. In the present application, the mixed solvent is used as a medium or a mixing medium for dissolving other components to ensure that the components can be evenly mixed.

[0021] In one or more technical solutions, the crosslinking agent is trimethylol melamine. Specifically, trimethylol melamine is used to enhance the crosslinking density inside the film and improve its physical stability, such as heat resistance and chemical resistance. In the present application, the crosslinking agent is in the range of 10-15 parts to achieve an ideal crosslinking effect. If the amount of the crosslinking agent exceeds 15 parts, the film may be too hard and lose the necessary flexibility; while if the crosslinking agent is less than 10 parts, the heat resistance and chemical resistance of the film may be insufficient.

[0022] In one or more technical solutions, the plasticizer is diisononyl phthalate. Specifically, the plasticizer is used to adjust the flexibility and processing properties of the film, making the film easier to handle without sacrificing its mechanical properties. In the present application, the plasticizer is in the range of 15-20 parts, which can balance the flexibility and mechanical strength of the film. If the amount of plasticizer exceeds 20 parts, the film may be too soft and easy to deform; if the amount of plasticizer is less than 15 parts, the film may be too hard and brittle and difficult to process.

[0023] In a second aspect, the present application provides a method for preparing the anti-glare film according to the first aspect, comprising the following steps:

[0024] According to the weight composition of the anti-glare film, the corresponding raw materials are prepared; the hydrophobic polycaprolactone copolymer is dissolved in a mixed solvent, tannic acid microspheres, a crosslinking agent, and a plasticizer are added, and ultrasonic mixing is performed at 65° C. for 15 minutes;

[0025] The mixture is coated on release paper to form a wet film; the film is placed in an oven for drying to obtain an anti-glare film.

[0026] In a third aspect, the present application provides an application of an anti-glare film, wherein the anti-glare film described in the first aspect or the anti-glare film prepared by the preparation method described in the second aspect is applied to a car cover.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The film described in the present application has a particle size of 10-50 μm of tannic acid microspheres, which can effectively scatter light inside the film, thereby reducing reflectivity and glare. When light hits the surface of the film, part of the light is scattered by these microspheres instead of being directly reflected back to the observer's eyes, which helps to reduce the glare caused by strong light or oncoming car lights when driving at night. At the same time, the hydrophobic polycaprolactone copolymer improves the hydrophobicity and weather resistance of the film by introducing perfluoropolyether segments.

[0029] The film described in this application, when applied to car covers, can significantly reduce glare and improve driving safety; improve heat insulation performance, help reduce the temperature inside the car and improve riding comfort; optimize the self-cleaning function and reduce maintenance costs. Therefore, the film described in this application can achieve a combination of efficient anti-glare and heat insulation effects without significantly affecting transparency. DETAILED DESCRIPTION

[0030] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0031] As used herein, "and / or" includes the term of all combinations of any one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.

[0032] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.

[0033] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.

[0034] Terminology explanation:

[0035] Perfluoropolyether carboxylic acid (PFPE-COOH) is a compound containing a perfluoropolyether segment (-CF2-CF2-) and a carboxyl group (-COOH). The perfluoropolyether segment gives the material extremely high hydrophobicity and oleophobicity, because the presence of fluorine atoms greatly reduces the surface energy. In the present invention, the perfluoropolyether carboxylic acid is used to be introduced into the polycaprolactone molecular chain through an esterification reaction to improve the hydrophobicity, weather resistance and mechanical properties of the final film.

[0036] Dicyclohexylcarbodiimide (DCC) is a commonly used dehydrating agent and is used as a condensing agent in organic synthesis. It can promote the esterification or amidation reaction between carboxylic acid and alcohol or amine. In the present invention, dicyclohexylcarbodiimide (DCC) is used to promote the esterification reaction between perfluoropolyether carboxylic acid and polycaprolactone, thereby introducing the perfluoropolyether chain segment into the polycaprolactone molecular chain.

[0037] Polycaprolactone (PCL-OH) is a biodegradable aliphatic polyester with good biocompatibility and processability. Polycaprolactone is polymerized from ε-caprolactone monomers and exhibits certain flexibility, solvent resistance and a low melting point. In the present invention, polycaprolactone is used as a base resin and is modified by introducing perfluoropolyether segments to improve its hydrophobicity and other physical properties.

[0038] Tannic acid (TA) is a natural polyphenol compound mainly found in plant tissues, such as oak bark, nut shells, etc. Tannic acid has strong antioxidant properties and can undergo cross-linking reactions with other compounds to form a network structure. In the present invention, tannic acid is used to prepare microspheres, which, as scatterers, can reduce light reflectivity, reduce glare, and improve thermal insulation performance.

[0039] Ethylene glycol diglycidyl ether (EGDE) is a bifunctional epoxy resin having two epoxy groups. It can undergo a ring-opening addition reaction with a compound containing active hydrogen (e.g., a hydroxyl group in tannic acid) to form a cross-linked network structure. In the present invention, ethylene glycol diglycidyl ether reacts with tannic acid to form a cross-linked network structure, and the formed tannic acid microspheres help to enhance the mechanical strength of the film and improve the optical properties.

[0040] Triphenylphosphine (TPP) is commonly used to promote various reactions in organic synthesis. In the present invention, triphenylphosphine is used as a catalyst for the reaction of tannic acid and ethylene glycol diglycidyl ether.

[0041] Trimethylolmelamine (TMM) is used to increase the cross-linking density inside the polymer, thereby improving the physical stability of the material, such as heat resistance and chemical resistance. In the present invention, it is used to enhance the physical stability of the anti-glare film.

[0042] Diisononyl phthalate (DINP), used to adjust the flexibility and processing properties of polymers, making the material easier to handle without sacrificing its mechanical properties. In the present invention, it is used to adjust the flexibility and processing characteristics of anti-glare films.

[0043] DMF (N,N-dimethylformamide), a commonly used polar aprotic solvent, is widely used in organic synthesis as a medium for dissolving other components.

[0044] THF (tetrahydrofuran) is commonly used as a solvent. In the present invention, it forms a mixed solvent with DMF to ensure that each component can be evenly mixed.

[0045] Preparation Example 1

[0046] The preparation method of the hydrophobic polycaprolactone copolymer comprises the following steps:

[0047] 30 g of perfluoropolyether carboxylic acid (10 mmol) was fully dissolved in 3000 mL of a mixed solvent of 1,3-bis(trifluoromethyl)benzene and THF in a weight ratio of 1:1;

[0048] Then, 2070 mg of dicyclohexylcarbodiimide (10 mmol) was added, the temperature was raised to 40° C., and the mixture was stirred for reaction for 2 hours under nitrogen protection; 80 g of polycaprolactone (1 mmol) was stirred to fully dissolve, and the mixture was stirred for reaction at 40° C. for 5 hours.

[0049] After the reaction was completed, the reaction mixture was poured into n-hexane to precipitate a white crude product. After filtering to remove the solvent, the product was dispersed in a mixed solvent of 1,3-bis(trifluoromethyl)benzene and ethanol (mass ratio 1:50) and filtered.

[0050] The solvent was then washed away with water, and after the water was dried, the mixture was placed in a vacuum oven and dried at 40° C. for 24 hours to obtain the final product - a hydrophobic polycaprolactone copolymer.

[0051] The hydrophobic polycaprolactone copolymer was tested by infrared spectroscopy, and the results were as follows:

[0052] At 1239cm -1 and 1189cm -1 A characteristic absorption peak belonging to CF appeared at , indicating that the perfluorinated chain segment was successfully introduced into the polycaprolactone molecular chain.

[0053] In the preparation method, polycaprolactone, Mn=8000 g / mol; perfluoropolyether carboxylic acid, model number is HEC-XF.

[0054] In the preparation method, the chemical equation involved is:

[0055]

[0056] Perfluoropolyether (PFPE) is a highly hydrophobic and oleophobic material, and the large number of CF bonds in its molecular chain gives it extremely low surface energy; in Preparation Example 1, the PFPE block is introduced into the end of the PCL macromolecular chain through an esterification reaction, so that hydrophobic groups are introduced into the PCL molecular chain, thereby improving the hydrophobic properties of the overall material.

[0057] Therefore, using hydrophobic polycaprolactone copolymer (PCL-6-PFPE) as the main resin of the car cover film not only has excellent hydrophobic properties, but also has good mechanical properties, thermal stability, chemical resistance, weather resistance and environmental protection performance, making it an ideal material for high-performance car cover films.

[0058] Preparation Example 2

[0059] The preparation method of tannic acid microspheres comprises the following steps:

[0060] Tannic acid and ethylene glycol diglycidyl ether are added in a molar ratio of 4:1, and triphenylphosphine is used as a catalyst (1% of the weight of tannic acid); tannic acid and ethylene glycol diglycidyl ether are dissolved in a mixed solvent of ethyl acetate and butyl acetate (the mixed solvent is ethyl acetate and butyl acetate mixed in a weight ratio of 1:1), triphenylphosphine is added, and the mixture is fully mixed. The mixture is reacted at room temperature for 24 hours. After the reaction is completed, the reaction liquid is centrifuged at a speed of 3000 rpm to collect microspheres; the microspheres are washed with deionized water and anhydrous ethanol in turn, and then freeze-dried for 24 hours to obtain tannic acid microspheres.

[0061] The prepared tannic acid microspheres were subjected to infrared spectroscopy detection, and it was found that:

[0062] At 2880cm -1 and 2960cm -1 The new signal peak generated at is attributed to the stretching of -CH2- in ethylene glycol diglycidyl ether, which proves that a chemical cross-linking reaction occurs between tannic acid and ethylene glycol diglycidyl ether.

[0063] CO group signal enhancement: at 1060cm -1 and 1240cm -1 The signal of the CO group at the position is significantly enhanced, which is attributed to the epoxy ring-opening reaction between the phenolic hydroxyl group of tannic acid and the epoxy group of ethylene glycol diglycidyl ether. The oxygen on the phenol reacts with the carbon on the epoxy group to form a chemical bond, which increases the proportion of the CO bond and thus enhances the vibration signal at this wavenumber.

[0064] Characteristic absorption peak of phenolic hydroxyl group: at 3400cm -1 The strong absorption peak at is attributed to the phenolic hydroxyl group of tannic acid, which indicates that the polyphenol structure of the prepared tannic acid microspheres is fully retained.

[0065] Example 1

[0066] An anti-glare film comprises the following raw materials in parts by weight:

[0067] 50 parts of hydrophobic polycaprolactone copolymer (from Preparation Example 1), 15 parts of tannic acid microspheres (from Preparation Example 2), 10 parts of a crosslinking agent (trimethylolmelamine), 15 parts of a plasticizer (diisononyl phthalate), and 120 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0068] The method for preparing the anti-glare film comprises the following steps:

[0069] According to the weight composition of the anti-glare film, the corresponding raw materials are prepared; the hydrophobic polycaprolactone copolymer is dissolved in a mixed solvent, tannic acid microspheres, a cross-linking agent, and a plasticizer are added, the temperature is raised to 65°C, ultrasonic oscillation is performed at 60 Hz for 15 minutes, and a wet film is applied on a release paper with a film thickness of about 200 μm; the film is transferred to an oven and the conditions are set to first dry at 50°C for 10 minutes and then dry at 80°C for 100 minutes to obtain an anti-glare film.

[0070] Example 2

[0071] An anti-glare film comprises the following raw materials in parts by weight:

[0072] 60 parts of hydrophobic polycaprolactone copolymer (from Preparation Example 1), 8 parts of tannic acid microspheres (from Preparation Example 2), 15 parts of a crosslinking agent (trimethylolmelamine), 20 parts of a plasticizer (diisononyl phthalate), and 150 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0073] The method for preparing the anti-glare film comprises the following steps:

[0074] According to the weight composition of the anti-glare film, the corresponding raw materials are prepared; the hydrophobic polycaprolactone copolymer is dissolved in a mixed solvent, tannic acid microspheres, a cross-linking agent, and a plasticizer are added, the temperature is raised to 65°C, ultrasonic oscillation is performed at 60 Hz for 15 minutes, and a wet film is applied on a release paper with a film thickness of about 200 μm; the film is transferred to an oven and the conditions are set to first dry at 50°C for 10 minutes and then dry at 80°C for 100 minutes to obtain an anti-glare film.

[0075] Example 3

[0076] An anti-glare film comprises the following raw materials in parts by weight:

[0077] 55 parts of hydrophobic polycaprolactone copolymer (from Preparation Example 1), 7 parts of tannic acid microspheres (from Preparation Example 2), 13 parts of a crosslinking agent (trimethylolmelamine), 17 parts of a plasticizer (diisononyl phthalate), and 135 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0078] The method for preparing the anti-glare film comprises the following steps:

[0079] According to the weight composition of the anti-glare film, the corresponding raw materials are prepared; the hydrophobic polycaprolactone copolymer is dissolved in a mixed solvent, tannic acid microspheres, a cross-linking agent, and a plasticizer are added, the temperature is raised to 65°C, ultrasonic oscillation is performed at 60 Hz for 15 minutes, and a wet film is applied on a release paper with a film thickness of about 200 μm; the film is transferred to an oven and the conditions are set to first dry at 50°C for 10 minutes and then dry at 80°C for 100 minutes to obtain an anti-glare film.

[0080] Example 4

[0081] An anti-glare film comprises the following raw materials in parts by weight:

[0082] 58 parts of hydrophobic polycaprolactone copolymer (from Preparation Example 1), 7 parts of tannic acid microspheres (from Preparation Example 2), 14 parts of a crosslinking agent (trimethylolmelamine), 19 parts of a plasticizer (diisononyl phthalate), and 140 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0083] The method for preparing the anti-glare film comprises the following steps:

[0084] According to the weight composition of the anti-glare film, the corresponding raw materials are prepared; the hydrophobic polycaprolactone copolymer is dissolved in a mixed solvent, tannic acid microspheres, a cross-linking agent, and a plasticizer are added, the temperature is raised to 65°C, ultrasonic oscillation is performed at 60 Hz for 15 minutes, and a wet film is applied on a release paper with a film thickness of about 200 μm; the film is transferred to an oven and the conditions are set to first dry at 50°C for 10 minutes and then dry at 80°C for 100 minutes to obtain an anti-glare film.

[0085] Example 5

[0086] An anti-glare film comprises the following raw materials in parts by weight:

[0087] 52 parts of hydrophobic polycaprolactone copolymer (from Preparation Example 1), 6 parts of tannic acid microspheres (from Preparation Example 2), 11 parts of a crosslinking agent (trimethylolmelamine), 16 parts of a plasticizer (diisononyl phthalate), and 126 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0088] The method for preparing the anti-glare film comprises the following steps:

[0089] According to the weight composition of the anti-glare film, the corresponding raw materials are prepared; the hydrophobic polycaprolactone copolymer is dissolved in a mixed solvent, tannic acid microspheres, a cross-linking agent, and a plasticizer are added, the temperature is raised to 65°C, ultrasonic oscillation is performed at 60 Hz for 15 minutes, and a wet film is applied on a release paper with a film thickness of about 200 μm; the film is transferred to an oven and the conditions are set to first dry at 50°C for 10 minutes and then dry at 80°C for 100 minutes to obtain an anti-glare film.

[0090] Comparative Example 1

[0091] An anti-glare film comprises the following raw materials in parts by weight:

[0092] 50 parts of a hydrophobic polycaprolactone copolymer (from Preparation Example 1), 10 parts of a crosslinking agent (trimethylolmelamine), 15 parts of a plasticizer (diisononyl phthalate), and 120 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0093] Other conditions are consistent with those in Example 1.

[0094] Comparative Example 2

[0095] An anti-glare film comprises the following raw materials in parts by weight:

[0096] 50 parts of hydrophobic polycaprolactone copolymer (from Preparation Example 1), 15 parts of tannic acid microspheres (from Preparation Example 2), 15 parts of plasticizer (diisononyl phthalate), and 120 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0097] Other conditions are consistent with those in Example 1.

[0098] Comparative Example 3

[0099] An anti-glare film comprises the following raw materials in parts by weight:

[0100] 50 parts of hydrophobic polycaprolactone copolymer (from Preparation Example 1), 15 parts of tannic acid microspheres (from Preparation Example 2), 10 parts of a crosslinking agent (trimethylolmelamine), and 120 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0101] Other conditions are consistent with those in Example 1.

[0102] Comparative Example 4

[0103] An anti-glare film comprises the following raw materials in parts by weight:

[0104] 50 parts of polycaprolactone (from Preparation Example 1), 15 parts of tannic acid microspheres (from Preparation Example 2), 10 parts of a crosslinking agent (trimethylolmelamine), 15 parts of a plasticizer (diisononyl phthalate), and 120 parts of a mixed solvent (DMF and THF in a mass ratio of 1:1).

[0105] Other conditions are consistent with those in Example 1.

[0106] The films prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to the following performance tests:

[0107] 1. Gloss test

[0108] The 60° specular gloss of the film to be tested was measured according to standard GB9754-88.

[0109] 2. Self-cleaning ability

[0110] Sprinkle simulated pollutants (corn starch) on the super-hydrophobic surface of the film to be tested, and then use a dropper to drop dyed deionized water on the surface to observe whether the water droplets can easily carry away the pollutant powder without any liquid residue.

[0111] Performance indicators: If water drops can easily remove the pollutant powder and no liquid remains on the membrane, it indicates that the membrane has good self-cleaning performance.

[0112] 3. Haze value

[0113] The haze of the film was measured using a haze meter.

[0114] Haze is defined as the percentage of light that is deflected more than 2.5° from the incident light direction to all transmitted light;

[0115] Therefore, high haze means that the surface or internal structure of the material can cause more light scattering. When light passes through a high haze material, the light does not pass directly through, but is scattered multiple times inside the material, making the light distribution more uniform; under strong light sources or high brightness environments, when the unscattered light directly hits the eyes, glare will be generated, causing visual discomfort. High haze materials reduce the generation of glare by scattering these direct light rays; high haze materials can transform point light sources or small area light sources into softer, more uniform surface light sources, thereby improving visual comfort and reducing eye fatigue.

[0116] 4. Light transmittance

[0117] The transmittance test was carried out using a UV-visible spectrometer to measure the transmittance of visible light in the wavelength range of 380 to 780 nm.

[0118] 5. Thermal insulation test

[0119] The test was carried out using an incubator with a foam insulation layer around and at the bottom, and a film prepared in Examples 1-5 and Comparative Examples 1-4 on the top. The size of the incubator was 50cmx20cmx20cm. A temperature probe was located at the center of the box, and a baffle was used to prevent direct light. The lighting source was a 250W infrared lamp with an irradiation distance of 25cm. The temperature differences inside and outside the incubator at 20min, 40min, and 60min were measured and calculated.

[0120] Table 1

[0121]

[0122] As shown in Table 1, the films of Examples 1-5 have high haze, low 60° gloss, good self-cleaning ability, high light transmittance, and excellent thermal insulation performance;

[0123] The high haze is manifested in that the haze values ​​of Examples 1-5 are 77.3%, 80.2%, 79.1%, 79.7% and 78.4%, respectively, which are significantly higher than those of Comparative Examples 1-4. This indicates that the film can effectively scatter light and reduce direct reflection, thereby reducing glare and improving visual comfort.

[0124] The lower 60° glossiness is shown in that the 60° glossiness values ​​of Examples 1-5 are 34.5%, 31.2%, 33.4%, 31.8%, and 34.1%, respectively, which are significantly lower than that of Comparative Example 1 (95.7%). The low glossiness of the film indicates that the surface reflects less light, further reducing the glare problem and improving driving safety and comfort.

[0125] The good self-cleaning ability is manifested in that no pollutants and liquid residues were found in the self-cleaning test of all embodiments, indicating that the film has excellent hydrophobic properties, which helps to reduce the adhesion of dust and stains and keep the surface clean.

[0126] The higher light transmittance is shown in that the visible light transmittance of Examples 1-5 is between 85.9% and 87.4%, ensuring good transparency.

[0127] Excellent thermal insulation performance. From the temperature difference between the inside and outside of the insulation box, Examples 1-5 show relatively good thermal insulation effect, especially at 60 minutes, the temperature difference value is excellent; this shows that the film can effectively block external heat transfer, reduce the temperature inside the car, and improve the riding comfort.

[0128] Comparative Example 1 lacks tannic acid microspheres, which results in poor anti-glare performance of the film. Its haze value is only 16.3%, which is significantly lower than 77.3% of Example 1. At the same time, the 60° glossiness is as high as 95.7%, which is much higher than 34.5% of Example 1. This shows that tannic acid microspheres are very important for improving the anti-glare performance of the film. In addition, the thermal insulation performance of Comparative Example 1 is also poor. The temperature difference between the inside and outside of the incubator is 10.6°C, 16.8°C and 19.5°C at 20 minutes, 40 minutes and 60 minutes, respectively, which are all lower than the data of Example 1 (15.2°C, 27.8°C and 31.5°C), indicating that tannic acid microspheres can also help enhance the thermal insulation effect.

[0129] Comparative Example 2 did not add a crosslinking agent. Although the film still maintained a relatively high haze value (74.7%) and a relatively low gloss (39.9%), the thermal insulation performance was reduced, and the temperature difference between the inside and outside of the thermal insulation box was slightly lower than that of Example 1. This shows that the crosslinking agent helps to further improve the physical stability of the film, especially the heat resistance and chemical corrosion resistance, thereby improving the overall thermal insulation effect.

[0130] Comparative Example 3 did not add plasticizer, and the haze value (66.9%) and glossiness (46.7%) of the film were lower than those of Example 1, and the self-cleaning ability was also worse, with a small amount of pollutants and liquid residues. This shows that plasticizers are important for adjusting the flexibility and processing properties of the film, and lack of plasticizers will affect the overall performance of the film.

[0131] Comparative Example 4 uses ordinary polycaprolactone instead of hydrophobic polycaprolactone copolymer. The haze value (62.5%) and glossiness (68.9%) of the film are significantly lower than those of Example 1, and the self-cleaning ability is the worst, with more pollutants and liquid residues. This shows the importance of hydrophobic polycaprolactone copolymer in improving the waterproof performance, weather resistance and mechanical properties of the film surface by introducing perfluoropolyether segments.

[0132] Therefore, through comparative examples 1-4 and example 1, it can be found that in the anti-glare film, the tannic acid microspheres scatter light to reduce glare and improve thermal insulation; the cross-linking agent enhances the stability of the internal structure of the film; the plasticizer improves the flexibility and processing properties of the film; and the hydrophobic polycaprolactone copolymer enhances the overall physical and chemical properties of the film.

[0133] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. An anti-glare film, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of hydrophobic polycaprolactone copolymer, 5-8 parts of tannic acid microspheres, 10-15 parts of cross-linking agent, 15-20 parts of plasticizer, and 120-150 parts of mixed solvent.

2. The anti-glare film according to claim 1, characterized in that: The preparation method of the hydrophobic polycaprolactone copolymer comprises the following steps: The perfluoropolyether carboxylic acid was dissolved, dicyclohexylcarbodiimide was added, the temperature was raised to 40°C under nitrogen protection, and the reaction was carried out at 40°C for 2 hours; polycaprolactone was continuously added, and the reaction was continued at 40°C for 5 hours. After the reaction was completed, post-treatment was carried out to obtain a hydrophobic polycaprolactone copolymer.

3. The anti-glare film according to claim 2, characterized in that: The molar ratio of the perfluoropolyether carboxylic acid, dicyclohexylcarbodiimide and polycaprolactone is 1:1:0.

1.

4. The anti-glare film according to claim 1, characterized in that: The particle size of the tannic acid microspheres is 10-50 μm.

5. The anti-glare film according to claim 1 or 4, characterized in that: The preparation method of the tannic acid microspheres comprises the following steps: Tannic acid and ethylene glycol diglycidyl ether were dissolved, triphenylphosphine was added, the mixture was fully mixed, and the mixture was reacted at room temperature for 24 hours. After the reaction, the reaction liquid was centrifuged at a speed of 3000 rpm, the microspheres were collected, and then post-processed to obtain tannic acid microspheres.

6. The anti-glare film according to claim 1, characterized in that: The mixed solvent is a mixed solvent composed of DMF and THF in a mass ratio of 1:

1.

7. The anti-glare film according to claim 1, characterized in that: The cross-linking agent is trimethylolmelamine.

8. The anti-glare film according to claim 1, characterized in that: The plasticizer is diisononyl phthalate.

9. The method for preparing the anti-glare film according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the weight composition of the anti-glare film, corresponding raw materials are prepared; a hydrophobic polycaprolactone copolymer is dissolved in a mixed solvent, tannic acid microspheres, a crosslinking agent, and a plasticizer are added, and ultrasonic mixing is performed at 65° C. for 15 minutes to obtain a mixture; The mixture is coated on release paper to form a wet film; the film is placed in an oven for drying to obtain an anti-glare film.

10. An application of an anti-glare film, characterized in that: The anti-glare film according to any one of claims 1 to 8 or the anti-glare film prepared by the preparation method according to claim 9 is applied to a car cover.